IMPLEMENTASI PERATURAN BUPATI KUTAI KARTANEGARA NOMOR 7 TAHUN 2012 TENTANG PEDOMAN PENYELENGGARAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KANTOR CAMAT LOA JANAN KABUPATEN KUTAI KARTANEGARA - Eka Zumaida Aprilia; Muhammad Noor; Rita Kalalinggi (Jurnal Paradigma (JP), 2021)
This article will discuss the implementation of policies related to PATEN services in the Loa Janan District. The research method uses descriptive qualitative. Sources of data come from observations, interviews, and literature studies. Data analysis used an interactive data analysis model. The results showed that the communication pattern carried out by Loa Janan District was quite good. The infrastructure facilities in Loa Janan District were quite good and adequate in implementing integrated administrative services. In terms of staff and abilities, it is still not ideal because there are officers who do not have the expertise appropriate to the field. Implementing officers have implemented transparency in the services provided to the community, but it has not been maximized because there are still people who feel discriminatory actions in delivering services. The existing procedures for the PATEN service in Loa Janan District are more concise and can bring benefits closer to the community.Keywords: implementasi, kebijakan, PATEN